Subliminal Message Social Media Against Trust Society About Spirit Doll ( Analysis Maqashid Sharia ) - Muhammad Syukri Albani Nasution; Hasnah Nasution; Imam El Islamy; Zulfikar Abdul Aziz; Wulan Dayu (Al-Mashlahah: Jurnal Hukum Islam dan Pranata Sosial, 2022)
This research is entitled subliminal social media message to public beliefs about spirit dolls using syariah maqashid analysis. The intensity of social media showing the spirit doll made most people start making excuses in finding the truth of their minds, so this study looks at how the secret message displayed by social media to the public in influencing their beliefs, as well as the position of sharia maqashid law used by some communities as evidence in its legitimacy. . The mixed method between qualitative and quantitative is a way to analyze this problem by looking at phenomena in the field and describing them and using questionnaires to see public perceptions. Cultivation, subliminal and maqashid theories are used as the basis of this research. There are secret messages displayed by the media to obscure the public's belief in the oneness of God that everything that is done should not be contrary to sharia law, let alone associating God.